GOVERNANCE REFORM: Citizen's Charter Model as Instument for Reform of Public Services-Based on Collaborative Governance: Learning From Blitar Indonesia and Chandigarh India - Muchamad Zaenuri (e-Publishing, 2013)
Reduction of bureaucratic domination of government in providing public services and public demands to the government, including local governments, to create a democratic public service is not negotiable. The local government responded through reform of governancee that are collaborative, involving civil society, one way in which public participation is to develop an instrument through service announcement (citizen's charter). With the formulation of local government edict, this service gives ample scope for the public to participate and perform control so that the public service that is responsive, transparent and accountable can be realized. Learning from the experience of Blitar Indonesia and India Chandigarh model of citizen's charter is proven to bring democratization of local public services. Constraints faced in this process include: lack of political will (political will) of the government, the failure of promotion, lack of professionalism and lack of participation of service providers from the public. To minimize the constraints faced by the need for collaborative care management as a form of public service management reform, which is still conventional? Keywords: Citizen's Charter, Local Government, Indonesia, India.